Relatedness of an RNA-binding motif in human immunodeficiency virus type 1 TAR RNA-binding protein TRBP to human P1/dsI kinase and Drosophila staufen. - Gatignol, A (1993)
TRBP is a human cellular protein that binds the human immunodeficiency virus type 1 TAR RNA. Here, we show that the intact presence of amino acids 247 to 267 in TRBP correlates with its ability to bind RNA. This region contains a lysine- and arginine-rich motif, KKLAKRNAAAKMLLRVHTVPLDAR. A 24-amino-acid synthetic peptide (TR1) of this sequence bound TAR RNA with affinities similar to that of the entire TRBP, thus suggesting that this short motif contains a sufficient RNA-binding activity. Using RNA probe-shift analysis, we determined that TR1 does not bind all double-stranded RNAs but prefers TAR and other double-stranded RNAs with G+C-rich characteristics. Immunoprecipitation of TRBP from human immunodeficiency virus type 1-infected T lymphocytes recovered TAR RNA. This is consistent with a TRBP-TAR ribonucleoprotein during viral infection. Computer alignment revealed that TR1 is highly homologous to the RNA-binding domain of human P1/dsI protein kinase and two regions within Drosophila Staufen. We suggest that these proteins are related by virtue of sharing a common RNA-binding moiety.